Beyond resistance: retheorizing indigenous media through production culture of Ghanaian language (Akan) commercial broadcasting - Frimpong, Nancy Achiaa, author; Chung, Hye Seung, advisor; Elkins, Evan, committee member; Aoki, Eric, committee member; Wolfgang, David, committee member (Colorado State University. Libraries, 2025)
This study examines organizational structure and production processes of indigenous language media (ILM), focusing on how these elements influence media operations and practices. By focusing on the operational dynamics of ILM in Ghana, this study provides a comprehensive understanding of the complex ways in which language, economy, and culture interact to construct a media system that emphasizes linguistic and discursive coexistence and fusion, rather than linguistic subjugation and indigenous media as a peripheral alternative discourse. This dissertation employs an interdisciplinary qualitative research approach, utilizing participant observation, practitioner interviews, informal conversations, and various reports to analyze two leading and competitive Ghanaian-owned commercial media corporations: Multimedia Group Limited (MGL) and Despite Media. Various theoretical frameworks from production studies, political economy, and heteroglossia are used to evaluate ILM's organizational structure and production process. This dissertation concludes that while indigenous media scholarship positions indigenous media as an alternative, oppositional category, a response to mainstream media, and a means of established resistance to a certain imperialism and misrepresentation (Spitulnik, 1999; De Jong, Shaw & Stammers, 2005), evidence from Ghana complicates this understanding, showing that indigenous media can simultaneously embody resistance and reinforce mainstream ideologies. This duality highlights the complex interconnectedness and interdependencies between local and global cultural forces, challenging the binary distinctions often present in discussions about indigenous media and reconfiguring ILM as more than just politically isolated productions of indigeneity. Additionally, the interplay between social, economic, cultural, religious, and political factors reinforces the existence of indigenous media in multiple formations with variegated practices, heightens their agenda-setting function, and possesses three significant interrelated characteristics of Akan commercial indigenous language media: bi-/multilingual discursivity, translational density, and audience-centricity. Hence, these findings underscore how media align with public values and community ethos, focusing on relationality and resonance, cultural narratives, and a commitment to lived realities and media responsibility. The findings suggest that while in the Western/European context, Indigenous media is political and marginalized, and a binary construct, indigenous language media in Africa is multifaceted, and has a dominant media status. Additionally, indigenous media and mainstream media should not be viewed as ideologically opposing entities. Rather, their positionality is intricately and inherently shaped by the specific mandates under which they operate, which subsequently delineate the ways their identities are marked and reinscribed by various geopolitical, cultural, economic, religious, and social factors. Hence, media practitioners, scholars, and policymakers must take cognizance of these defining forces to better understand the media landscape.
Keywords: indigenous language media; political economy; Telenovela/Twinovela; indigenous/ethnic/minority media; Akan news and journalism; production studies